Formulation of bacterial consortium for improvement growth and yield of maize (Zea mays L.) - Ikhwan, Ali; Iriany, Aniek; Ishartati, Erny; Hasanah, Faridlotul (Sains Tanah : Jurnal ilmu Tanah dan Agroklimatologi, 2021)
Plant growth-promoting bacteria (PGPB) have become an important subject of research to increase maize production. The PGPB consortium should provide more benefits than single or dual inoculation. This study aimed to investigate the effect of a PGPB consortium on improving maize growth and yield. The field experiment used a split-plot design. The main plot consisted of three maize varieties (Talenta, Pertiwi-3, and Bisma), and the subplot consisted of three formulations of PGPB consortia [endophytic bacteria isolates, Acetobacter sp., cellulolytic, and ligninolytic (F1); endophytic bacteria isolates, Azospirillum sp., cellulolytic, and ligninolytic (F2); and endophytic bacteria isolates, cellulolytic, ligninolytic, Acetobacter sp., and Azospirillum sp. (F3)] and one control. PGPB consortia formulation did not influence maize growth significantly, but maize varieties did. Pertiwi-3 showed the highest value in all growth variables, followed by Bisma and Talenta, respectively. The effect of PGPB consortia formulation upon ear fresh and dry weight depends upon the maize variety, and Pertiwi-3 showed the highest value in yield variables. PGPB consortia formulation 2 was the most effective to apply for Pertiwi-3 cultivation, while PGPB consortia formulation 3 produced higher yields for Talenta and Bisma. These findings indicated that specific PGPB formula could improve the yield for specific maize varieties.